Analysis Of Training And Development Of Labor In Baznas, Sumedang Regency - Dewi Puspasari (SINTESA, 2023)
This research is entitled analysis of training and development of labor in baznas, sumedang regency .The goal to be achieved in this research is to find out what form of training and development is provided by BAZNAS Sumedang Regency to amil and to see how much knowledge is applied human resource science management in the training and development function workforce in BAZNAS Sumedang Regency. The research data were obtained from interviews, observations, documentation, and literature. Manpower training and development has an important meaning for BAZNAS Sumedang Regency. With training and development workforce, it is hoped that organizational goals can be achieved effectively and efficient